Characteristics of Submicron-footprint TiO2 based AlGaN/GaN MOSHEMT on SiC Substrate - Meng Di; Lin Shuxun; Wen, Cheng P.; Wang Maojun; Wang Jinyan; Hao Yilong; Zhang Yaohui; Lau, Kei May; Wu Wengang (2013 IEEE INTERNATIONAL CONFERENCE OF ELECTRON DEVICES AND SOLID-STATE CIRCUITS (EDSSC), 2013)
AlGaN/GaN metal-oxide-semiconductor high electron mobility transistors (MOSHEMTs) with thick (>30 nm), high-kappa (TiO2/NiO), submicron-footprint (0.4 mu m) gate dielectric on SiC substrate are demonstrated, which are found to exhibit low gate leakage current (similar to 1 nA/mm of gate periphery), high I-MAX (1 A/mm), and high drain breakdown voltage (188 V). The derived current gain cutoff frequency is 30 GHz (from S-parameter measurements). The output power density is 6.6 W/mm, and the associated power-add ed-efficiency is 46% at 2.5 GHz frequency and 50 V drain bias. This high performance submicron-footprint MOSHEMT is highly promising for microwave power amplifier applications in communication and radar systems.